2009
DOI: 10.1007/s00464-008-0255-8
|View full text |Cite
|
Sign up to set email alerts
|

Is endoscopic band ligation superior to injection therapy for Dieulafoy lesion?

Abstract: Our study suggests that of the endoscopic treatment methods, band ligation is superior to injection therapy for the treatment Dieulafoy lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 15 publications
0
34
0
10
Order By: Relevance
“…İnvazif olmayan tekniklerle yeterli tedavinin sağlanamadığı hastalarda cerrahi tedavi seçenekleri düşünülmelidir. [3,6,7] Bu çalışmanın amacı üst GİS kanaması nedeniyle endoskopik tanı ve tedavi uyguladığımız DL tanısı almış hastaların analizini yapmak, bu hastaların klinik ve epidemiyolojik bulgularını belirlemek, uygulanan tedavileri ve sonuçlarını geriye dönük olarak incelemektir.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…İnvazif olmayan tekniklerle yeterli tedavinin sağlanamadığı hastalarda cerrahi tedavi seçenekleri düşünülmelidir. [3,6,7] Bu çalışmanın amacı üst GİS kanaması nedeniyle endoskopik tanı ve tedavi uyguladığımız DL tanısı almış hastaların analizini yapmak, bu hastaların klinik ve epidemiyolojik bulgularını belirlemek, uygulanan tedavileri ve sonuçlarını geriye dönük olarak incelemektir.…”
Section: Resultsunclassified
“…[1] Üst GİS kanamalarının yaklaşık %0,3-6,7'sinden sorumludur. [6][7][8] Genellikle hasta hikayesinde NSAİİ ilaç kullanımı sayısı 4 (1-9) idi. En sık uygulanan iki tedavi yönte-mi olan enjeksiyon tedavisi+hemoklips uygulaması ve tek başına hemoklips uygulaması yapılan hastaların klinik karşılaştırmaları Tablo 3'de verilmiştir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…To date, the majority of studies have focused on success with a given treatment or monitoring modality [34][35][36][37][38]. Some studies have found the mechanical method to be more effective, resulting in primary hemostasis in over 90 % of patients [34,36], while several others have found combination therapy with epinephrine injection and thermocoagulation or mechanical treatment to be more effective for maintaining hemostasis than epinephrine injection alone [34,35,38,39]. Although there is no general agreement on treatment of choice for bleeding DL, our results were consistent with pervious findings in that we observed less rebleeding in patients who underwent combination therapy in the patient population we examined.…”
Section: Discussionmentioning
confidence: 99%
“…Electrocautery should be applied with firm pressure, optimally using low power (15 Watts) of longer duration (10 to 12 seconds) [59] . Treatment should be repeated until flattening of the vessel or coagulation of the stigmata [60] .…”
Section: Endoscopic Treatment Modalitiesmentioning
confidence: 99%